Unveiling the Potential of Silymarin, Spirulina platensis, and Chlorella vulgaris towards Cardiotoxicity via Modulating Antioxidant Activity, Inflammation, and Apoptosis in Rats - Hanem F. El-Gendy; Hanem K. Khalifa; Ahmed Omran; Reda M. S. Korany; Shaimaa Selim; Eman Hussein; Rashed A. Alhotan; Anam Ayyoub; Shimaa R. Masoud (Life)
This study assessed the possible pharmacological effects of Chlorella vulgaris (Cg), Spirulina platensis (St), and silymarin (Sl) against thioacetamide (TA)-induced cardiotoxicity in rats, with a focus on their antioxidant, cardioprotective, and anti-inflammatory properties. The following is the random grouping of sixty male rats into six groups of ten animals each: the control (negative control), TA-intoxicated group (positive control; 300 mg/kg body weight (BW)), Sl + TA group (100 mg Sl/kg BW + TA), St + TA group (400 mg St/kg BW + TA), Cg + TA (400 mg Cg/kg BW + TA), and St + Cg + TA group (400 St + 400 Cg mg/kg BW + TA) were all administered for 30 days. At the start of the study, groups 2 through 6 were administered TA intraperitoneally at a dosage of 300 mg/kg BW for two consecutive days, with a 24 h gap between each dose, to induce cardiac damage. Blood samples were obtained to measure hematological parameters and perform biochemical assays, including lipid profiles and cardiac enzymes. For histopathology and immunohistochemistry determination, tissue samples were acquired. The current findings showed that TA injection caused hematological alterations and cardiac injury, as evidenced by greater serum levels of troponin I, creatine kinase-MB, and total creatine kinase (p < 0.05), as well as significantly elevated serum malondialdehyde and decreased serum total antioxidant capacity (p < 0.05) concentrations. Moreover, an increase in blood low-density lipoprotein and total cholesterol concentration (p < 0.05) was recorded in the TA group. There were alterations in the heart tissue’s histological structure of the TA group compared to the control ones. These alterations were characterized by vacuolar degeneration of myocytes, loss of cross striation, coagulative necrosis, and fibrosis of interstitial tissue, which was ameliorated by the supplementation of SI, St, and Cg. The TA-intoxicated group showed weak expression of B-cell lymphoma protein 2 (p < 0.05) and strong immunoreactivity of tumor necrosis factor-α and B-cell lymphoma protein 2-associated X (p < 0.05). However, the groups receiving Sl, St, and Cg experienced the opposite. The administration of Sl, St, Cg, and St + Cg along with TA significantly improved and restored (p < 0.05) erythrogram indices, including RBCs, hemoglobin, total leukocytic count, lymphocytes, and monocyte, to the normal control values. The administration of Sl, St, and Cg alleviated the cardiotoxicity caused by TA via reducing oxidative stress, inflammatory markers, and apoptosis in heart tissue. In summary, the current findings suggest that the treatment with Sl, St, and Cg was beneficial in ameliorating and reducing the cardiotoxicity induced by TA in rats.